Analisis Komparatif Desain Konstitusional Indonesia dan Amerika Serikat terhadap Optimalisasi Fungsi Wakil Presiden dalam Sistem Pemerintahan - M Yahya Wahyudin; M Rio Dozan; Uu Nurul Huda (Jurnal Hukum Lex Generalis, 2026)
This study analyzes the optimization of the vice president's function in the presidential system through a comparative analysis of the Indonesian and United States Constitutions. Using normative legal research methods with a comparative-functional design, this study identifies three main dimensions: (1) constitutional design shows that Indonesia has minimal and ambiguous provisions on the vice president's role in Article 4 paragraph (2) of the 1945 Constitution, while the United States provides a more detailed framework through Article I, II, and Amendment 25; (2) checks and balances mechanisms in Indonesia involve the DPR-MK-MPR but are weakened by supermajority coalition dominance, contrasting with the United States' more balanced two-party system; (3) optimization requires constitutional reform, strengthening accountability mechanisms, and adapting Indonesia's sociopolitical context. This study recommends amendments to the 1945 Constitution or enactment of specific legislation on presidential institutions, granting the vice president roles in coalition coordination and regional development, and strengthening public accountability. In conclusion, optimizing the vice president's function is crucial for strengthening constitutional democracy and improving governance quality in Indonesia.